L’Orazio di Nisbet – Rudd. Riflessioni sull’arte del commentare - Paolo Fedeli (Exemplaria Classica, 2009)
Nisbet-Rudd Commentary on III Horace's book of Carmina is the starting point for a reflection upon the contemporary commentaries and upon the commentary technique.